A implementação da reorientação curricular em Iporá- Goiás, na perspectiva dos professores de Ciência do 6° ao 9° ano - PONTES, Ueslene Maria Ferreira (2011)
This study aims to examine process of implementation of the Reorientation Course in the State of Goiás from the perspective of science teachers in the city of Iporá GO. Whereas the proposed changes to the curriculum aims to meet the requirements of funding agencies and who often come to teachers without discussion and without consideration of their reality, analysis and reflection on the vision of these teachers regarding these proposed changes in their practice is of crucial importance since it is the teacher who runs, experiences and identifies the effects of this deployment. This is survey was conducted with science teachers from the 6th to 9th grade public school state Iporá -Goiás, and the instruments used were the questionnaire and semi structured interviews. Through these instruments have sought to know, first, what is the understanding of teachers about the process of implementing the Curriculum Reorientation in Goiás during the period 2004 to 2010, and identify which are the participating teachers‟ conceptions regarding the science curriculum, and know what changes are already effective in the practice of these teachers. As proposed intervention, this study aims to seek subsidies for training of teachers regarding the implementation of these changes in their practice based on the Reorientation Course. We performed a brief analysis of Reports "Resume Debate on" material that contains the proposal of the Curriculum Reorientation and was distributed by the Ministry of Education of Goiás to all public schools. The results of this study indicate that despite the expiration of seven years the process of reorientation Course there are still many doubts, many mistakes, shortcomings and difficulties to implement the changes suggested by the proposal. Thus, this research concluded that there must be more time for discussion and study on the curriculum for initial training, plus conditions for the creation of study groups by area for discussions and exchanges of experiences.